Correlates of moral development in juvenile delinquents - Veneziano, Carol (American journal of criminal justice, 1988)
Moral reasoning and development have been the focus of considerable research in the past two decades, stimulated primarily by Kohlberg’s formulation of the stages of moral development. Studies of juvenile delinquents have indicated that youthful offenders are at lower developmental stages of moral reasoning than their nondeliquent counterparts. Some research has also examined patterns among juvenile delinquents with respect to moral judgments, as it is recognized that they are heterogeneous as a group. In order to further examine correlates of moral judgments among juvenile delinquents, a sample of 411 adolescent offenders was obtained. The sample consisted of all adjudicated male delinquents aged twelve to fifteen admitted to a state training school over a sixteen month period of time. Data was obtained on a measure of moral judgment, the Morality-Immorality Scale (Baker, Stewart, Kaiser, Brown & Barclay, 1979), along with a variety of measures of personality, behavioral, social, intellectual and educational skills. The adolescents were divided into three groups based on their scores on the MIS. The highest scoring group on MIS had better scores on a variety of behavioral, intellectual and personality indicators, while the lowest scoring group had the worst scores on such measures. Moral-religious emphasis in the home was not associated with the scores on the Morality-Immorality Scale, but a measure of family pathology was negatively related to these scores. Implications of the findings for research and for the development of moral education programs for delinquents is discussed.